2018
DOI: 10.1016/j.ridd.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Predicting reading ability in teenagers who are deaf or hard of hearing: A longitudinal analysis of language and reading

Abstract: BackgroundDeaf and hard of hearing (D/HH) children and young people are known to show group-level deficits in spoken language and reading abilities relative to their hearing peers. However, there is little evidence on the longitudinal predictive relationships between language and reading in this population.AimsTo determine the extent to which differences in spoken language ability in childhood predict reading ability in D/HH adolescents.Methodsand procedures: Participants were drawn from a population-based coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…The normally hearing comparison group had been identified using an algorithm developed by the investigators based on the dates of birth of the required number of children with normal hearing within each district and for each screening period. Further assessment of the sample was undertaken in the Hearing Outcomes at Teen Age project at a mean age of 16.9 (SD: 1.4) years [18][19][20][21][22][23][24].…”
Section: Study Background and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The normally hearing comparison group had been identified using an algorithm developed by the investigators based on the dates of birth of the required number of children with normal hearing within each district and for each screening period. Further assessment of the sample was undertaken in the Hearing Outcomes at Teen Age project at a mean age of 16.9 (SD: 1.4) years [18][19][20][21][22][23][24].…”
Section: Study Background and Samplementioning
confidence: 99%
“…Written informed consent was obtained from the teenage participants and their principal caregivers. Full details on the tracing and recruitment procedures of the children with PCHL and children with normal hearing and the measures used to assess outcomes during adolescence are reported elsewhere [18][19][20][21][22][23][24].…”
Section: Study Background and Samplementioning
confidence: 99%
“…Akan tetapi Tuli memiliki perbendaharaan kata yang cukup terbatas, 8 sehingga ada kemungkinan kesulitan dalam memahami isi bacaan seperti pada booklet. 9 Metode ceramah hadir sebagai metode sehari-hari yang digunakan guru di sekolah. Siswa Tuli, melalui metode ini, diharapkan mampu menyesuaikan diri dalam kelompok sosial dengan terbiasa membaca gerakan bibir lawan bicara (lip-reading).…”
Section: Pendahuluanunclassified
“…reading outcomes. For example, Worsfold and colleagues studied older British children with hearing losses ranging from moderate (40-69 dB) to profound (�95 dB) who used spoken language (n = 53) and found that spoken language skills at age eight best predicted reading comprehension in adolescence [16]. While the relationship between spoken language skills and reading outcomes is not surprising, it does support the contention that underlying language skills are strongly associated with print literacy development in deaf, as well as hearing, children.…”
Section: Introductionmentioning
confidence: 99%